PENINGKATAN KESELAMATAN BAGI PENGENDARA DAN PEJALAN KAKI DI DUSUN TRAJENG, DESA PAKISJAJAR, KECAMATAN PAKIS, KABUPATEN MALANG - Abbas, Muhammad Hasyim Ibnu; Sari, Gladis Viona Putri Permata; Afrizal, Wafiq Sajidhan; Pamungkas, Demas Hadi; Pujiana, Eri (LPPM Institut Pendidikan Nusantara Global, 2024)
Trajeng Hamlet has 2 schools, 1 orphanage, and 1 Quranic Learning Center (TPQ), namely MI Al Hasib Pakis, TK Muslimat NU 8 Asshofiyah, Nurul Hadi Orphanage, and TPQ Al-Azhar. Observations reveal that the hamlet lacks traffic signs, which are crucial for road safety. The absence of traffic signs poses significant risks to road users, especially in a community with schools and children actively commuting. This work program focuses on addressing this issue by providing traffic signs as essential road infrastructure. The program is implemented through several stages: observation, problem identification, permit acquisition, and execution. These steps ensure that the planned facilities are properly integrated into the hamlet's road network and meet community needs. Beyond implementation, continuous education is necessary. Village authorities are encouraged to conduct regular awareness programs for residents about the importance of traffic signs and their meanings. Such programs can foster better understanding and adherence to traffic regulations. Additionally, educating parents and guardians to prevent underage driving is vital in enhancing safety.